CHALLENGES FACED BY EFL STUDENTS IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Atrianus Toni (Pedagogic Research-Applied Literacy Journal, 2026)
English has become a global language of considerable importance; however, learning English as a Foreign Language (EFL) remains challenging for many students in non-English-speaking countries. This study aims to identify and analyze the key challenges faced by EFL students in learning English as a foreign language. Employing a descriptive qualitative research design, the study involved undergraduate EFL students majoring in English education. Data were collected through questionnaires and semi-structured interviews and analyzed using thematic analysis. The findings reveal three major categories of challenges: linguistic challenges (grammar, vocabulary, pronunciation, and listening comprehension), psychological challenges (anxiety, low motivation, and lack of self-confidence), and pedagogical challenges (limited exposure to authentic English input and teacher-centered instructional practices). These challenges were found to be interrelated and collectively hinder students’ ability to develop communicative competence. The study concludes that addressing EFL learning difficulties requires an integrated pedagogical approach that simultaneously targets linguistic development, affective support, and instructional practices.